Walking on the Moon: A randomized clinical trial on the role of lower body positive pressure treadmill training in post-stroke gait impairment - Calabrò, Rocco Salvatore (J Adv Res, 2019)
Body weight–supported treadmill training (BWSTT) can be usefully employed to facilitate gait recovery in patients with neurological injuries. Specifically, lower body positive pressure support system (LBPPSS) decreases weight-bearing and ground reaction forces with potentially positive effects on qualitative gait indices. However, which gait features are being shaped by LBPPSS in post-stroke patients is yet poorly predictable. A pilot study on the effects of LBPPSS on qualitative and quantitative gait indices was carried out in patients with hemiparesis due to stroke in the chronic phase. Fifty patients, who suffered from a first, single, ischemic, supra-tentorial stroke that occurred at least 6 months before study inclusion, were enrolled in the study. They were provided with 24 daily sessions of gait training using either the AlterG device or conventional treadmill gait training (TGT). These patients were compared with 25 age-matched healthy controls (HC), who were provided with the same amount of AlterG. Qualitative and quantitative gait features, including Functional Ambulation Categories, gait cycle features, and muscle activation patterns were analyzed before and after the training. It was found that AlterG provided the patients with higher quantitative but not qualitative gait features, as compared to TGT. In particular, AlterG specifically shaped muscle activation phases and gait cycle features in patients, whereas it increased only overall muscle activation in HC. These data suggest that treadmill gait training equipped with LBPPSS specifically targets the gait features that are abnormal in chronic post-stroke patients. It is hypothesizable that the specificity of AlterG effects may depend on a selective reshape of gait rhythmogenesis elaborated by the locomotor spinal circuits receiving a deteriorated corticospinal drive. Even though further studies are warranted to clarify the role of treadmills equipped with LBPPSS in gait training of chronic post-stroke patients, the knowledge of the exact gait pattern during weight-relief is potentially useful to plan patient-tailored locomotor training.